A Survey on The Use of Social Media as a Medium in Learning Writing Skills - Afrianto Daud; Hafizah Salsabila Ali; Edwar Kemal (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2021)
This study aimed to investigate the use of social media as a medium in learning writing skills. The subjects of this survey study were 124 second-year students of the English Study Program, Faculty of Teachers Training and Education, Universitas Riau (2019 batch) selected using the total sampling technique. There were 85 out 124 students who completed the questionnaire. Data were analyzed using descriptive statistics in the form of frequencies and percentages. This study showed that the kinds of social media that are commonly used in learning writing are Twitter, YouTube, Instagram, WhatsApp, and Facebook. Some specific writing skills learned through social media claimed by the respondents included learning new vocabulary, grammatical structure, correct spelling, paragraph development, correct capitalization, correct punctuation, unified ideas, and coherent ideas. Respondents also reported that they used social media for several purposes: adding references and information, taking as learning resources, developing creativity, collecting assignments, conducting online discussion, exchanging learning materials with classmates, and sending material in learning writing skills. It can be concluded social media has been part of significant alternative learning media used by students to improve their writing skills.